Lifestyle factors and prostate-specific antigen (PSA) testing in UK Biobank: Implications for epidemiological research. (December 2016) - Littlejohns, Thomas J.; Travis, Ruth C.; Key, Tim J.; Allen, Naomi E.
Highlights: Prostate-specific antigen (PSA) testing is key in diagnosing prostate cancer. Risk factors for prostate cancer were related to the likelihood of PSA testing. There is potential for detection bias in epidemiological studies of prostate cancer. Abstract: Background: The central role of prostate-specific antigen (PSA) testing in the diagnosis of prostate cancer leads to the possibility that observational studies that report associations between risk factors and prostate cancer could be affected by detection bias. This study aims to investigate whether reported risk factors for prostate cancer are associated with PSA testing in a large middle-aged population-based cohort in the UK. Methods: The cross-sectional association between a wide range of sociodemographic, lifestyle, dietary and health characteristics with PSA testing was examined in 212, 039 men aged 40–69 years in UK Biobank. Results: A total of 62, 022 (29%) men reported they had ever had a PSA test. A wide range of factors was associated with a higher likelihood of PSA testing including age, height, education level, family history of prostate cancer, black ethnic origin, not being in paid/self-employment, living with a wife or partner, having had a vasectomy, being diagnosed with cancer or hypertension and having a high dietary intake of cereal, cooked and salad/raw vegetables, fresh fruit and tea. Conversely, socioeconomic deprivation, Asian ethnic origin, current smoking, low alcohol intake, high body-mass index, high coffee consumption and being diagnosed with diabetes, heart disease or stroke were associated with a lower likelihood of PSA testing. Conclusions: A variety of sociodemographic, lifestyle and health-related characteristics are associated with PSA testing, suggesting that observed associations of some of these traits with risk for prostate cancer in epidemiological studies may be, at least partially, due to detection bias.